2017
DOI: 10.1016/j.vaccine.2016.09.068
|View full text |Cite
|
Sign up to set email alerts
|

Root cause analysis underscores the importance of understanding, addressing, and communicating cold chain equipment failures to improve equipment performance

Abstract: HighlightsEighty-six refrigerators were evaluated for non-performance in Mozambique and Uganda.Communicating equipment failures resulted in actions that addressed failures.Systematic monitoring, failure analysis, and reporting strengthen the cold chain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 11 publications
0
19
0
5
Order By: Relevance
“…The monitoring of immunobiological conservation is part of ensuring the maintenance of the immunogenic power of these inputs, conferred by the producing laboratory, and must be ensured by means of appropriate structure and procedures, in order to ensure effective results in the practice of immunization (13,14,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The monitoring of immunobiological conservation is part of ensuring the maintenance of the immunogenic power of these inputs, conferred by the producing laboratory, and must be ensured by means of appropriate structure and procedures, in order to ensure effective results in the practice of immunization (13,14,24).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Zaragoza (Spain) identified that an electrical power system would prevent economic loss for the NIP resulting from the interruption in the cold chain by cutting off the electrical power (8). Besides, the absence of an alternative energy supply source has been associated with exposure of immunobiologicals to temperatures outside the limits (4,24). Therefore, a no-break or a generator is required to compensate the shortcomings of the electrical network (9).…”
Section: Discussionmentioning
confidence: 99%
“…National immunization staff and procurement officers may consider the value of cold chain equipment that is designed to avoid freezing and to operate successfully in areas without reliable access to electricity [20] (Franzel et al). Program managers may find it surprising to know that their investigations of equipment failures can yield valuable and actionable information for technicians, procurement officers, equipment manufacturers, and international partners [22].…”
Section: Logistics Datamentioning
confidence: 99%
“…10,19,20 These findings highlight the need to develop local infrastructures to coordinate resources and ensure accountability. 17,18 Finally, key factors in the effective use of RTMDs include training staff members on device maintenance and data interpretation and developing standard procedures for responding to alarms. Without the underpinning of appropriately trained and resourced cold-chain staff members, RTMD use alone will not be sufficient to ensure that vaccines are stored under the correct conditions to preserve potency.…”
Section: Lessons Learned and Recommendationsmentioning
confidence: 99%
“…10,19,20 These findings highlight the need to develop local infrastructures to coordinate resources and ensure accountability. 17,18…”
Section: Lessons Learned and Recommendationsmentioning
confidence: 99%